2018
DOI: 10.1038/s41467-018-02986-7
|View full text |Cite
|
Sign up to set email alerts
|

Residential energy use emissions dominate health impacts from exposure to ambient particulate matter in India

Abstract: Exposure to ambient fine particulate matter (PM2.5) is a leading contributor to diseases in India. Previous studies analysing emission source attributions were restricted by coarse model resolution and limited PM2.5 observations. We use a regional model informed by new observations to make the first high-resolution study of the sector-specific disease burden from ambient PM2.5 exposure in India. Observed annual mean PM2.5 concentrations exceed 100 μg m−3 and are well simulated by the model. We calculate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
180
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 185 publications
(199 citation statements)
references
References 60 publications
13
180
4
2
Order By: Relevance
“…Previous studies that evaluated Indian scenarios (GBD MAPS Working Group, ; International Energy Agency, , ; Pommier et al, ) used relatively coarse spatial resolution (0.5° × 0.5° or 0.5° × 0.67°) chemical transport models to estimate the impacts on PM 2.5 concentrations per scenario, where the GBD MAPS Working Group then applied the fractional impacts on higher resolution ambient PM 2.5 concentrations to estimate the impacts on health. Model simulations using emissions at these resolutions have been shown to have discrepancies relative to observations (Moorthy et al, ; Pan et al, ; Pommier et al, ), while higher resolution models have been found to produce PM 2.5 concentrations in closer agreement to observations (Conibear et al, ; Kumar et al, ; Saikawa et al, ). Previous studies analyzing the current contributions of different emission sources in India found residential energy use (RES) emissions to dominate, with substantial contributions from power generation (ENE), industry (IND), and land transport (TRA) Conibear et al, ; GBD MAPS Working Group, ; Lelieveld et al, ; Silva et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies that evaluated Indian scenarios (GBD MAPS Working Group, ; International Energy Agency, , ; Pommier et al, ) used relatively coarse spatial resolution (0.5° × 0.5° or 0.5° × 0.67°) chemical transport models to estimate the impacts on PM 2.5 concentrations per scenario, where the GBD MAPS Working Group then applied the fractional impacts on higher resolution ambient PM 2.5 concentrations to estimate the impacts on health. Model simulations using emissions at these resolutions have been shown to have discrepancies relative to observations (Moorthy et al, ; Pan et al, ; Pommier et al, ), while higher resolution models have been found to produce PM 2.5 concentrations in closer agreement to observations (Conibear et al, ; Kumar et al, ; Saikawa et al, ). Previous studies analyzing the current contributions of different emission sources in India found residential energy use (RES) emissions to dominate, with substantial contributions from power generation (ENE), industry (IND), and land transport (TRA) Conibear et al, ; GBD MAPS Working Group, ; Lelieveld et al, ; Silva et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Model simulations using emissions at these resolutions have been shown to have discrepancies relative to observations (Moorthy et al, ; Pan et al, ; Pommier et al, ), while higher resolution models have been found to produce PM 2.5 concentrations in closer agreement to observations (Conibear et al, ; Kumar et al, ; Saikawa et al, ). Previous studies analyzing the current contributions of different emission sources in India found residential energy use (RES) emissions to dominate, with substantial contributions from power generation (ENE), industry (IND), and land transport (TRA) Conibear et al, ; GBD MAPS Working Group, ; Lelieveld et al, ; Silva et al, ). Ambient PM 2.5 ‐related premature mortality in India has been found to be responsive to reductions in SO 2 emissions, with little sensitivity to NH 3 emissions (Lee et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[100][101][102] Compared to conventional porous air filters, nanofiber filters structured by electrospinning offer higher performance due to large surface-to-volume ratio, tailored pore size, and high permeability. To achieve efficient removal of PMs and toxic gases, the design of air filters with high selectivity and low cost has drawn considerable attention.…”
Section: Air Pollutant Filtrationmentioning
confidence: 99%